Classification of Hydraulic Cements Used in Dentistry - Camilleri, Josette (Frontiers in Dental Medicine, 2020)
Since their introduction in clinical dentistry, hydraulic cements have gained popularity. Their applications are diverse. Their usefulness is due to their hydraulic nature in that they do not deteriorate when wet, which is important for a number of clinical applications, as is the formation of calcium hydroxide as a by-product of the hydration reaction of the calcium silicates. The first hydraulic cement was a simple mixture of Portland cement, as used in the construction industry, with bismuth oxide to increase its radio-opacity. Regardless of being a hydraulic calcium silicate, it was initially incorrectly labelled as a phosphate cement misleadingly called “mineral trioxide aggregate”. Since then, beneficial clinical applications have led to the development of a number of materials with a different base, alternative vehicles, and incorporating modifiers of various kinds. Given the variety, and possible confusion, a rational classification of hydraulic cements used in dentistry is necessary. The classification is primarily dependent on the context in which the materials are used as this informs the user about the environment and possible interactions. Secondly, a classification based on the material constitution is given as knowledge of its chemistry will help predict behaviour, identify risks, and thus facilitate selection and handling.